Overactivity of the Less Affected Side as a Possible Pattern of Asymmetry in Sitting in Patients Suffering from First-Time Ischemic Stroke—An Observational Study - Agata Zdrowowicz-Doroz; Jakub Stolarski; Karolina Krzysztoń; Izabela Domitrz; Jan Kochanowski (Brain Sciences, 2023)
It has been observed that in some people in the acute phase of ischemic stroke (IS) there is a tendency to shift the body weight towards the side more affected by the disease and a tendency to spontaneous movements of the upper and/or lower limbs (not covered by the neurological syndrome). The purposes of this study were: to define the kind of behavior observed, and to select symptoms which can predict its occurrence. Participants (n = 222) hospitalized due to first-time IS were assigned to three groups. A: 78 patients with no lateralization of the neurological syndrome (lateralization of the neurological syndrome—LoNS); B: 109 patients with LoNS; O+ group: 35 patients, who at the beginning of hospitalization presented, apart from LoNS, characteristic motor symptoms performed by the less affected side. Patients underwent therapy depending on the neurological symptoms. If the patient showed potential symptoms of a new phenomenon, overactivity of the less affected side (OLAS), a trial therapy (focused on this behavior) was used to confirm it. The predictive symptoms, selected among these from the index day, for the occurrence of OLAS in sitting were distinguished: asymmetry in supine posture and simple, repetitive movements of the nonparetic upper extremity.